NMR study of paramagnetic chemical shifts of [Dy(DTPA)]2− at various concentrations in solution - Zapolotsky, E.N.; Chuikov, I.P.; Zhang, Jinsheng; Babailov, S.P. (Polyhedron, 2025)
The longitudinal relaxation rates of signals in the NMR spectra of the [Dy(H2O)n(DTPA)]2− complex are sensitive to concentration changes due to Curie-spin contribution to the lanthanide-induced enhancement in the spin-spin relaxation rate, with the one is predominant in the region of high concentrations and low temperatures. [Display omitted] The [Dy(H2O)n(DTPA)]2− complex was studied in aqueous solution by 1H NMR at different temperatures and concentrations. It was experimentally found that the longitudinal relaxation rates of signals in the NMR spectra of the [Dy(H2O)n(DTPA)]2− complex are sensitive to concentration changes. It was found that the Curie-spin contribution to the lanthanide-induced enhancement in the spin–spin relaxation rate is dominant in the region of high concentrations and low temperatures. The complex can be considered as a promising NMR/MRI probe and reagent for in vitro and in vivo determination of temperature in aqueous media, as well as for temperature control during in situ studies of exothermic or endothermic processes.